Design and development of DNA biosensors based on silver nanoclusters and hybridisation chain reaction - Wong, Zheng Wei (2023)
Biosensors that couple hybridisation chain reaction amplification and fluorogenic silver nanoclusters (HCR-AgNCs) have the potential to enable simple and cost-effective detection of target analytes. These biosensors feature non-enzymatic amplification at mild conditions with a strong label-free fluorescence response. Whilst the proof-of-concept of these sensors have been promising, the design and developmental stages of HCR-AgNCs biosensors remain a challenge due to the lack of studies within the field itself.